Ischaemic Tolerance and the Effect of Ageing Using a Rodent Donation after Circulatory Death (DCD) Model. (July 2018) - Chew, Hong Chee; Villanueva, Jeanette; Gao, Ling; Doyle, Aoife; Hicks, Mark; Jabbour, Andrew; Dhital, Kumud; Macdonald, Peter
Abstract : To investigate the effect of ageing on donor heart recovery after exposure to DCD withdrawal in a rodent model. Method: Wistar rats (3, 12, 18 and 24 months) were anaesthetised and instrumented for invasive blood pressure and continuous heart rate/saturation monitoring using pulse oximetry. Circulatory death was induced by asphyxiation via tracheal ligation followed by injection of 500IU heparin via the renal vein. 3 month rats were exposed to 12 minutes warm ischaemia time (WIT). All other groups were exposed to 20 minutes WIT. At the end of the fixed WIT, hearts were flushed with 100mLs of celsior (C) or supplemented celsior(Cs) solution (containing erythropoietin, glyceryl trinitrate and zoniporide), followed by reperfusion on ex-vivo perfusion rig with oxygenated Krebs buffer at 37oc for 15 minutes followed by 'working' mode for 30mins. Aortic flow (AF), heart rate (HR) and pressure (MAP) were measured using PowerLab™; coronary flow (CF) was measured at 5 minute intervals. Results: HR and MAP recovery were similar in all groups. CF and AF recovery are presented below: All results were corrected to heart weight[SVMHS1].CF was poorest in 3C group when compared to all other groups. AF recovery was superior in both 12mo groups when compared to other age groups (P<0.05); and all Cs groups show better AF recovery when compared to C only group. (P<0.05) Figure. No caption available. Conclusion: These results suggest that myocardial tolerance to WIT increases through adolescence into adulthood then declines through the process of ageing. It is important to note, however, all age groups showed improved recovery after WIT with pharmacological supplementation.